Alternativas para el control biologico del pulgon pardo de los ciricos (Toxoptera citricidus kirkaldy)(Homoptera: Aphididae) - Peña, E.=700 1 Villazon, L.; Jimenez, S.; Vazquez, L.; Licor, L.
(Es, En)
Ilus., 11 ref.
Keywords: TOXOPTERA CITRICIDUS; CONTROL BIOLOGICO; HONGOS ENTOMOPATOGENOS; EXTRACTOS VEGETALES; AZADIRACHTA INDICA; MELIA AZEDARACH; CITRUS; CUBA; VIRUS DE LA TRISTEZA DE LOS CITRICOS